Impact of coronary collateralization on major adverse cardiovascular and cerebrovascular events after successful recanalization of chronic total occlusion - Sun, Yurong; Zhang, Bin; Zhang, Xinyuan; Zhang, Xiaojiao; Bao, Wenqi; Bai, Hangrui; Luan, Bo (Frontiers in Cardiovascular Medicine, 2024)
Aims: To investigate the effects of coronary collateral circulation (CCC) on the prognosis of chronic total occlusion (CTO) patients with or without metabolic syndrome (MetS).The study included 342 CTO patients who underwent successful percutaneous coronary intervention (PCI) at the People's Hospital of Liaoning Province between February 1, 2021 and September 30, 2023. Rentrop score was used to assess the status of CCC. The outcome was major adverse cardiovascular and cerebrovascular events (MACCEs). MACCEs, defined as a composite of all-cause mortality, cardiac death, non-fatal myocardial infarction (MI), target vessel revascularization, and nonfatal stroke. Univariate and multivariate logistic were used to investigate the association of CCC, MetS, and MACCEs, with odds ratio (OR) and 95% confidence interval (CI).The effect of CCC were further investigated in different MetS, diabetes mellitus (DM), and Syntax score groups.Results: MACCEs were more common in patients with poor CCC than in good CCC (38.74% vs 16.56%). Statistical differences were found in MACCEs (OR=3.33, 95%CI:1.93-5.72), MI (OR=3.11, 95%CI: 1.73-5.58), target vessel revascularization (TVR) (OR=3.06, 95%CI: 1.70-5.53), and stent thrombosis (OR=6.14, 95%CI: 2. 76-13.65) between the good and the poor CCC groups. Poor CCC patients with MetS were associated with higher incidence of MACCEs (OR=4.21, 95%CI: 2.05-8.65), non-fatal MI (OR=4.44, 95%CI: 2.01-9.83), TVR (OR=3.28, and stent thrombosis (OR=10.80,. Similar findings were also found in CTO CCC on the prognosis of CTO patients with or without MetS 3 patients with DM and Syntax score ≥23. Conclusion: Poor CCC could increase the risk of MACCEs in CTO patients, particular in patients who have MetS, DM, and Syntax score ≥23. Further prospective, multicenter studies are needed to validate our findings and explore potential therapeutic interventions.